2022
DOI: 10.3390/ijerph19073869
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Music Tempo on Fatigue Perception at Different Exercise Intensities

Abstract: Background: This study aimed to clarify the effect of music tempo on runners’ perception of fatigue at different exercise intensities and while listening to music of different tempos through running experiments. Methods: This study used a within-subject two-factor experimental design with music tempo (fast music, slow music, no music) and exercise intensity (high intensity, low intensity) as independent variables and the time to fatigue perception (TFP), the difference in heart rate (HR) and the difference in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…The music stimuli included fast and slow tempos. Fast tempo music was strong at a beat of 150–160 bpm; whereas slow tempo music was between a narrow range, soft, soothing, and a beat of 90–100 bpm ( Karageorghis et al, 2008 ; Wu et al, 2022 ). Based on previous studies ( Karageorghis and Jones, 2014 ; Grgic, 2022 ), one fast and one slow tempo were selected and played repeatedly at an intensity of 75 dBA.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The music stimuli included fast and slow tempos. Fast tempo music was strong at a beat of 150–160 bpm; whereas slow tempo music was between a narrow range, soft, soothing, and a beat of 90–100 bpm ( Karageorghis et al, 2008 ; Wu et al, 2022 ). Based on previous studies ( Karageorghis and Jones, 2014 ; Grgic, 2022 ), one fast and one slow tempo were selected and played repeatedly at an intensity of 75 dBA.…”
Section: Methodsmentioning
confidence: 99%
“…Based on previous studies ( Karageorghis and Jones, 2014 ; Grgic, 2022 ), one fast and one slow tempo were selected and played repeatedly at an intensity of 75 dBA. The selected music was relatively simple, without lyrics, and had an upbeat style and obvious rhythm to stimulate positive emotions ( Karageorghis and Jones, 2000 ; Wu et al, 2022 ). This simple music removed personalized preferences and was more universal; simple music helped participants improve performance in repetitive endurance exercises, music without lyrics reduced the influence of lyrical content, and obvious rhythm reduced participants’ relative oxygen uptake during the experiment ( Terry et al, 2012 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A growing body of research has demonstrated the impact of music on physiological variables, including blood pressure, heart rate respiration rate, body temperature [16], and biochemical parameters, in addition to pain sensitivity [17]. Furthermore, music has a positive effect on athletic performance, by delaying fatigue and increasing work capacity [18]. In the context of resistance training, research also indicates an ergogenic effect of listening to music.…”
Section: Introductionmentioning
confidence: 99%
“…Electromyography (EMG) and electrocardiography (ECG) are two commonly used measures for fatigue detection. Wu et al studied the effect of musical rhythm on the subjective and objective fatigue of runners at different exercise intensities using EMG [ 3 ]. Butkevičiūtė used ECG for the identification of fatigue [ 4 ].…”
Section: Introductionmentioning
confidence: 99%